STUDENTS’ WRITING DESCRIPTIVE TEXT TOWARDS ONLINE EXPERIMENTAL MODEL AT GRADE XI SMA N 1 BATANGTORU - Agustiani, Ayu (jurnalalfa, 2024)
The purpose of this study was to determine the ability students to write descriptive text using online experimental model at grade XI students of SMA N 1 Batangtoru. To obtain research data, researcher used pre-test and post-test.Research data collection used quantitative methods, the data on the number of students’ in the class is 10 students’. The result of the researcher showed that SMA N 1 Batangtoru accepted and used online experimental model well at school. To collected the data, the researcher was used classroom action research that consist of planing, acting, observing, and reflecting. Based on the analyzed, it can be found that (1) the scores students’ writing descriptive text before by using online experimental model at grade XI SMA N 1Batangtoru is 55,5 (2) the scores students’ writing descriptive text after by using online experimental model at grade XI SMA N 1 Batangtoru is 74,00, (3) writing difficulties descriptive text.